Optimizing Sensorial Attributes and Consumer Preference through Oat Beta Glucan Enrichment in Chocolate Flavored Milk - Bandana Chatterjee (Science and Technology - Recent Updates and Future Prospects Vol. 3, 2024)
Nowadays, the consumption of milk is declining at a fast rate whereas on the contrary there is a rise in the consumption of carbonated beverages which in turn increases the obesity rate. It has also been seen that there is an increasing prevalence of cardiovascular disease (CVD), so there is a need to identify functional foods that reduce CVD risk factors. Innovative approaches to milk fortification hold promise not only in enhancing nutritional value but also in addressing the challenge of declining milk consumption, particularly among children. The study aims to provide insights into the efficacy of oat beta-glucan fortification in enhancing the nutritional profile and consumer appeal of milk-based products, hence promoting cardiovascular health and overall well-being. Research has shown that there is a strong association between oat beta-glucan consumption and a decrease in blood cholesterol levels. Ideal carriers of bioactive compounds are milk-based beverages. Amongst other compounds, beta-glucan is a viscous soluble dietary approved by the FDA that can lower serum cholesterol. Sensory evaluation was carried out for consumer preference and the texture and viscosity were also measured. After a few days, the product taste and viscosity have not changed and there is no separation observed. So, milk and milk products fortified with oat beta-glucan will help to reduce coronary heart disease (CHD) and other health issues. The sources of oat beta-glucan include oat bran, oatmeal and rolled oats which are generally consumed as breakfast cereals, biscuits, bread etc.